Auditoría financiera a la empresa de televisión por cable Cocateve s.a. de la ciudad del Coca, período 2017 - Salguero Bonilla, Jessica Jomaira (2021)
ABSTRACT The research work topic was "FINANCIAL AUDIT OF THE TELEVISION COMPANY BY CABLE COCATEVE SA, PERIOD 2017". It was carried out to improve the company's processes and know the financial situation of the same; thus, be able to determine the existing deficiencies to issue a report with the respective conclusions and recommendations to provide solutions to existing problems in the company. The present investigative work is organized as follows: The research work begins with the Statement of the Problem, which will explain what the research problem is about, a justification, and the project's respective objectives. Subsequently, the Theoretical Framework is presented, which is composed of four main topics. The first will describe the company's generalities and, consequently, various topics that will refer to the research project's theoretical guidelines. Consecutively, the Methodology is presented, how this investigation was developed, where the type of investigation, the population, and the sample, techniques, and instruments for collecting, processing, and interpreting data were defined. Regarding the processing and discussion of results, those obtained from the Financial Audit's execution carried out on December 31, 2017, are reflected, whose execution is supported by the respective file through the working papers. Finally, the conclusions and recommendations obtained in the result of the execution of the investigative work will be presented. Keywords: Audit, financial audit, financial statements, accounting records, assets, liabilities. Reviewed by: Dr. Narcisa Fuertes, PhD. ENGLISH PROFESSOR cc: 1002091161